Association of the P6 Protein of Cauliflower mosaic virus with Plasmodesmata and Plasmodesmal Proteins . Issue 3 (19th September 2014) - Rodriguez, Andres; Angel, Carlos A.; Lutz, Lindy; Leisner, Scott M.; Nelson, Richard S.; Schoelz, James E.
Abstract : Inclusion bodies of Cauliflower mosaic virus function in delivery of virions to the plasmodesma for transport to adjacent cells . Abstract: The P6 protein of Cauliflower mosaic virus (CaMV ) is responsible for the formation of inclusion bodies (IB s), which are the sites for viral gene expression, replication, and virion assembly. Moreover, recent evidence indicates that ectopically expressed P6 inclusion-like bodies (I-LB s) move in association with actin microfilaments. Because CaMV virions accumulate preferentially in P6 IB s, we hypothesized that P6 IB s have a role in delivering CaMV virions to the plasmodesmata. We have determined that the P6 protein interacts with a C2 calcium-dependent membrane-targeting protein (designated Arabidopsis [ Arabidopsis thaliana ] Soybean Response to Cold [AtSRC2.2]) in a yeast ( Saccharomyces cerevisiae ) two-hybrid screen and have confirmed this interaction through coimmunoprecipitation and colocalization assays in the CaMV host Nicotiana benthamiana . An AtSRC2.2 protein fused to red fluorescent protein (RFP ) was localized to the plasma membrane and specifically associated with plasmodesmata. The AtSRC2.2-RFP fusion also colocalized with two proteins previously shown to associate with plasmodesmata: the host protein Plasmodesmata-Localized Protein1 (PDLP1) and the CaMV movement protein (MP ). Because P6 I-LB s colocalized with AtSRC2.2 and the P6 protein had previously been shown to interact with CaMV MP, we investigated whether P6 I-LB s might also be associated with plasmodesmata. We examined the colocalization of P6-RFP I-LB s with PDLP1-green fluorescent protein (GFP) and aniline blue (a stain for callose normally observed at plasmodesmata) and found that P6-RFP I-LB s were associated with each of these markers. Furthermore, P6-RFP coimmunoprecipitated with PDLP1-GFP. Our evidence that a portion of P6-GFP I-LB s associate with AtSRC2.2 and PDLP1 at plasmodesmata supports a model in which P6 IB s function to transfer CaMV virions directly to MP at the plasmodesmata.